Welding of 42SiCr High-Strength Steel - Pekovic, Michal; Jenicek, Stepan; Rubesova, Katerina; Vorel, Ivan; Jirkova, Hana (Manufacturing Technology Journal, 2018)
Various industry sectors are using advanced high-strength steels nowadays. Application of these steels are often constrained by the capabilities of their manufacturing and processing technologies. To deliver the required properties, advanced high-strength steels must possess the prescribed microstructures which can be achieved by specific heat treatment routes, such as intercritical annealing or the Q&P process. Difficulties, however, arise in these materials' joining, and welding in particular. Welding profoundly affects the microstructure and mechanical properties of the product due to the amount of heat input and subsequent rapid cooling. For these reasons, laser welding and electron beam welding tests were carried out on experimental 42SiCr steel. Prior to welding, the material was treated using two different Q&P process sequences and one conventional quenching sequence. The weld metal, the heat affected zone and the base material were examined by metallographic methods and the impact of the introduced heat on the microstructure was studied.
Keywords: welding; laser; electron beam; AHSS steel; mechanical tests